Current status of the assessment of sarcopenia, frailty, physical performance and functional status in chronic kidney disease patients. Issue 1 (January 2022) - Otobe, Yuhei; Rhee, Connie M.; Nguyen, Matthew; Kalantar-Zadeh, Kamyar; Kopple, Joel D.
Abstract : Purpose of review: Low physical function, frailty, and sarcopenia are common complications of chronic kidney disease (CKD). In this article, we review the epidemiology and pathogenesis of low physical function, as well as its associations with adverse outcomes in CKD patients. Additionally, we present various traditional and novel methods for assessment of physical function in CKD patients. Recent findings: In nondialysis dependent (NDD) and dialysis-dependent CKD patients, the prevalence of low physical function, frailty, and sarcopenia are substantially higher than in the general population. The potential mechanisms of low physical function, frailty, and sarcopenia in CKD patients are due to various factors including underlying kidney disease, co-existing comorbidities, and certain therapeutic interventions utilized in CKD. Increasing evidence has also uncovered the ill effects of impaired physical function on clinical outcomes in CKD patients. Summary: Routine assessment of physical function is an under-utilized yet important component in the management of CKD patients. Future studies are needed to determine how prescription of exercise and increased daily physical activity can be tailored to optimize the health and well-being of NDD and dialysis-dependent CKD patients in pursuit of successful aging.